Online and Face-to-Face Performance on Two Cognitive Tasks in Children With Williams Syndrome - Ashworth, Maria; Palikara, Olympia; Burchell, Elizabeth; Purser, Harry; Nikolla, Dritan; Van Herwegen, Jo (Frontiers in Psychology, 2021)
There has been an increase in cognitive assessment via the internet, especially since the coronavirus disease 2019 (COVID-19) increased the need for remote psychological assessment. This is the first study to investigate the appropriability of conducting cognitive assessments online with children with a neurodevelopmental condition and intellectual disability, namely, Williams syndrome (WS). This study compared Raven’s Coloured Progressive Matrices (RCPM) and British Picture Vocabulary Scale (BPVS) scores from two different groups of children with WS age 10 – 11 years who were assessed online (n= 14) or face-to-face (RCPM n= 12; BPVS n= 24). Bayesian t-tests showed children’s RCPM scores were similar across testing conditions, but suggested BPVS scores were higher for participants assessed online. The differences between task protocols are discussed in line with these findings, as well as the implications for neurodevelopmental research.